Prevalensi Karies dan Erosi pada Narapidana Pengguna Narkotika Jenis Sabu-Sabu di Lembaga Pemasyarakatan Klas II-A Kabupaten Jember - Syeifira Salsabila; Hestieyonini Hadnyanawati; Erawati Wulandari (Fakultas Kedokteran Gigi Universitas Jember, 2021)
The problem of methamphetamine abuse in Indonesia is still very concerning even though the prohibition on consuming narcotics outside of medical indications has been regulated in law. Methamphetamine users are at high risk for tooth decay, tooth decay that often occurs in methamphetamine users is caries and erosion. This is because the abuse of methamphetamine can affect the oral hygiene and saliva quality of the users. Given the high risk of methamphetamine users being exposed to caries and erosion, researchers need to conduct research that aims to determine the prevalence of caries and erosion, as well as describe the characteristics of inmates who use shabushabu narcotics in the Class II-A Penitentiary Office Jember. There are 58 respondents in this study. Caries measurement was carried out using the DMF-T index, erosion measurement was carried out using the Basic Erosive Wear Examination, while the characteristics of the respondents were obtained through a questionnaire sheet. The result is that the prevalence of caries in methamphetamine users is 89.66% with a mean DMF-T score of 7.21 and the prevalence of erosion is 72.41% with a mean erosion score of 5.29. It can be concluded that most users of methamphetamine have caries and erosion problems in their teeth.